The Alps as barrier to dispersal in cold-adapted freshwater fishes? Phylogeographic history and taxonomic status of the bullhead in the Adriatic freshwater drainage - Slechtová, Vendula; Bohlen, Jörg; Freyhof, Jörg; Persat, Henri; Delmastro, Giovanni B (Molecular phylogenetics and evolution, 2004)
The freshwater faunas of the Italian peninsula are isolated from the rest of Europe by the geographic barrier of the Alps and consequently have developed many endemic forms and contain few non-endemic species. However, some 'non-endemics' may either represent recent invaders of the Adriatic basin or cryptic endemic species. To test these two hypotheses against each other, we studied the origin and phylogenetic relationships of bullheads, cold adapted freshwater fishes of the genus Cottus, from both sides of the Alps and Dinaric Mountains. From the Adriatic basin, Cottus ferrugineus () was described as an endemic species, but the present analyses of sequences of the complete mitochondrial control region of 146 individuals from 43 localities showed no major differentiation between bullheads from both sides of the Alps. The very low diversification between representatives across the Alps suggests active transfers of haplotypes across this geographic barrier from the glacial cycles up to recent times. The transfers are most likely based on stream capture, since the cold-adapted bullhead is able to colonise the highest stretches of the water courses. No other freshwater fish in Europe is known to have experienced such an extensive gene flow across the highest European Mountains. In contrast, the Dinaric Mountains seem to have been a much more effective barrier between the Danube and the Adriatics. Our data reject the hypothesis of C. ferrugineus as an endemic species in the whole Adriatic drainage.
Keywords: Animals; Base Sequence; Geography; DNA, Mitochondrial; shluková analýza; Molecular Sequence Data; Italy; Fishes; Itálie; fyziologická adaptace; DNA primery; zeměpis; ryby; Cold Temperature; Fresh Water; Phylogeny; Genetics, Population; molekulární sekvence - údaje; populační genetika; sladká voda; Haplotypes; Sequence Alignment; mitochondriální DNA; sekvence nukleotidů; Adaptation, Physiological; Sequence Analysis, DNA; DNA Primers; zvířata; haplotypy; sekvenční analýza DNA; nízká teplota; fylogeneze; Cluster Analysis; Demography; sekvenční seřazení; demografie